Correlation Between C-Reactive Protein Level and Outcome In Coronavirus Disease 2019 Patients At COVID Intensive Care Unit RSUP. Dr. M. Djamil Padang - Putri Ariani; Dedy Kurnia; Malinda Meinapuri; Rudy Afriant; Rina Gustia; Rikarni; Rinal Effendi (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is a respiratory system disease transmitted to humans and has infected humans in almost every country. Plasma cytokine levels, such as C-reactive protein (CRP), are elevated inflammatory markers in most COVID-19 patients and are routinely examined, especially in the intensive care Unit (ICU). Elevated CRP levels are associated with higher rates of severity and death. Objective: This study aimed to determine the correlation between CRP levels and outcomes in COVID-19 patients at COVID ICU RSUP. Dr. M. Djamil Padang Period July – December 2021. Method: This research was conducted using by analytic observational method with a retrospective cohort design. Secondary data was collected from the medical records of COVID-19 patients treated in the ICU COVID RSUP. Dr. M. Djamil Padang from July – December 2021, using total sampling as a technique, 107 samples met the inclusion criteria. Data analysis was carried out using univariate and bivariate methods. Result: The result shows more male patients (51.4%) than women (48.6%). From the age range, most age was found in the range > 59 years (54.2%). The most common type of comorbid disease was diabetes (32.7%). The highest CRP level at the initial ICU admission was >160 mg/L (70.1%), and the highest ferritin level was >434 ng/mL (86.0%). The most common patient outcome was death (65.4%). There is a relationship between CRP levels (p = 0.029) and the outcome of COVID-19 patients in the COVID ICU. Conclusion: This study concludes that there is a correlation between C-Reactive Protein (CRP) levels and Outcomes in COVID-19 patients at COVID ICU RSUP. Dr. M. Djamil Padang Period July – December 2021. Keywords : COVID-19, CRP, Patient Outcome, ICU